Protocol for a first-in-human feasibility study of T regulatory cells (TR004) for inflammatory bowel disease using (ex vivo) Treg expansion (TRIBUTE) - Jennifer Clough; Peter Irving; A Toby Prevost; Graham M Lord; Joana Vasconcelos; James B Canavan; Beverley Rodger; D Macallan (BMJ Open)
Introduction Crohn’s disease (CD) is a chronic, immune-mediated inflammatory bowel disease (IBD), presenting with symptoms of abdominal pain and bleeding from the gastrointestinal tract. There is no known cure. In vitro-expanded ‘thymus-derived’ regulatory T cells (tTreg) have shown promise in preclinical models of IBD, leading to interest in their use as a potential therapy in CD. We present a study protocol for a first-in-human study of Tregs for IBD using ex vivo Treg expansion. This study will explore the preliminary safety and tolerability of a single dose of Treg immunotherapy and will inform the design of a subsequent larger trial.Methods and analysis Four patients will be recruited from gastroenterology clinics at Guy’s and St Thomas’ NHS Foundation Trust. Eligible participants are those who are at least 18 years old, have a diagnosis of active moderate to severe CD and have failed to respond to or tolerate at least two prior lines of standard medication. Participants receive a single dose of autologous ex vivo-expanded Tregs and will be followed up to week 21 to collect safety and exploratory efficacy data. Additional safety monitoring will occur at 1 and 2 years post-dose. The primary endpoint is defined as the occurrence of dose-limiting toxicity occurring within 5 weeks post-infusion.Ethics and dissemination The study protocol and related documents have been approved by a NHS Research Ethics Committee, the Health Research Authority and the Medicines and Healthcare products Regulatory Agency for Clinical Trial Authorisation. It is intended that the results of the trial will be presented at international conferences and will be submitted for publication in a peer-reviewed scientific journal.Trial registration number NCT03185000